Traumatic rupture of hepatic hydatid cyst in children. - Lizaso, Isabel; Benedictti, Juan L (Cirugía del Uruguay, 1985)
Three cases of traumatic rupture of hepatic hydatid cyst in children are presented. Low frequency of complications in infantile hepatic hydatid cysts is pointed out, traumatic rupture due to the anatomic and the cyst characteristics al this age being predominan!.